PENERAPAN PIDANA PADA PENGULANGAN PENGGUNAAN NARKOTIKA BAGI PENYALAHGUNA PASCA REHABILITASI - Linda Ikawati (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2022)
Narcotics are addictive substances that generally affect consciousness and have side effects in causing severe dependence on the user. So with this it is not imaginary to make users justify any means to get it back to satisfy this dependence. The use of narcotics is strictly prohibited in Indonesia, thus making a special classification for anyone involved in narcotics crime to facilitate the imposition of sanctions and it is hoped that with this classification the sanctions imposed are more targeted. This study uses a normative juridical method which refers to secondary data in the form of normative rules, both laws and regulations, doctrines, theories, and results from other researchers. In this study, it was found that the perpetrators of repeated use of narcotics for post-rehabilitation abusers were classified as abusers so that according to Article 127 of the Narcotics Law, apart from having to carry out the rehabilitation process, they must also continue to carry out the rest of the crime as regulated in the article which has been decided by a judge who has persists.